Assesmen indek kerentanan pantai Kabupaten Rembang, Jawa Tengah - Iryanthony, Sigit Bayhu; Santoso, Budi; Hartanto, Pungki (Jurnal Geografi : Media Informasi Pengembangan dan Profesi Kegeografian, 2018)
Indonesia is an archipelago country that has the longest coastline after Canada (UNCLOS). Rembang District is a coastal area in Northern Java, which has a very dynamic development because of its location of the capital city that located along the coastal area. The purpose of this study is to assess the degree of coastal vulnerability in Rembang District with the higher level of development. The CVI method (Coastal Vulnerability Index) of evisien sting is used to assess vulnerability. The coastal vulnerability is very low over 8 km, with a 15.4% of coastal length of Rembang District. Low vulnerability occurs in areas that are located in areas close to settlements area, with beaches already experiencing human intervention. The low category is about 12 km long, reaching 23.3% of the existing coastal length in Rembang District. The middle category is about 16 km, equivalent to 30.8% of shoreline. While the high category is about 10 km, equivalent to 19.2% of coastal length. The highest category has a length of 6 km, equivalent to 11.5% of the coastal area of Rembang district.